Dihydroartemisinin Inhibits the Proliferation of Esophageal Squamous Cell Carcinoma Partially by Targeting AKT1 and p70S6K - Zhu, Lili; Chen, Xinhuan; Zhu, Yanyan; Qin, Jiace; Niu, Tingting; Ding, Yongwei; Xiao, Yang; Jiang, Yanan; Liu, Kangdong; Lu, Jing; Yang, Wanjing; Qiao, Yan; et al. (Frontiers in Pharmacology, 2020)
Dihydroartemisinin (DHA), a sesquiterpene lactone with endoperoxide bridge, is one of the derivatives of artemisinin. In addition to having good antimalarial properties, DHA exhibits anticancer effects including breast cancer and lung cancer. However, the mechanism of DHA inhibiting the progression of esophageal cancer, especially esophageal squamous cell carcinoma (ESCC), is unclear. In this study, DHA was found to inhibit the proliferation of ESCC, and we explored the underlying molecular mechanisms. DHA had the ability of inhibiting esophageal cancer cell proliferation and anchorage-independent growth. Flow cytometry analysis revealed that DHA can significantly block cell cycle in the G1 phase. The results of human phospho-kinase array revealed that DHA can downregulate the expression levels of p70S6KT389 and p70S6KT421/S424. Furthermore, the expression levels of mTORS2448, p70S6KT389, p70S6KT421/S424 and RPS6S235/S236 were decreased by treatment of DHA in KYSE30 and KYSE150 cells.We then explored the proteins targeted by DHA to inhibit the mTOR-p70S6K-RPS6 pathway. Results of in vitro kinase assay revealed that DHA significantly inhibited phosphorylation of mTORS2448 by targeting AKT1and p70S6K kinase. In vivo, DHA inhibited the tumor growth of ESCC patient-derived xenograft and weakened p-mTOR, p-p70S6K, and p-RPS6 expression in tumor tissues. Altogether, our results indicated that DHA has anti-proliferative effects in ESCC cells and can downregulate mTOR cascade pathway by binding with AKT1 and p70S6K. Thus, DHA has great potential for the prevention or treatment of ESCC.